Attributes And Adoption Of Mobile Commerce In Malaysia - Sadrzadeh, Sarvnaz (2008)
This study is attempts to provide empirical data on Malaysia's perception towards mobile commerce and factors that may influence to accept or delay the acceptance of this technology.